PEMANFAATAN LAHAN SUB-OPTIMAL UNTUK PENGUSAHAAN TANAMAN KARET: SUATU RANGKUMAN HASIL SURVEI DAN PENELITIAN - PA Nugroho (Talenta Publisher, 2015)
Some typologies of the sub-optimal area are known as the potential for rubber cultivation. Tidal and high elevation areas are the two potential for rubber cultivation. Rubber cultivation in these areas must be followed by the input of technology. In this paper, we summarize the results of the research and survey from the Indonesian Rubber Research Institute in order to support the utilization of the sub-optimal area for rubber cultivation. Water management, modification of planting material and modification in planting manner are needed for rubber cultivation in the tidal area while rubber development in an area with high elevation; the selection of appropriate rubber clones and soil conservation techniques are required.